2016
DOI: 10.1038/srep22733
|View full text |Cite
|
Sign up to set email alerts
|

Variations in SXT elements in epidemic Vibrio cholerae O1 El Tor strains in China

Abstract: Vibrio cholerae O1 El Tor biotype strains are responsible for three multiyear epidemics of cholera in China during the seventh ongoing pandemic. The presence of the integrative conjugative element SXT is strongly correlated with resistance to nalidixic acid, tetracycline, and trimethoprim-sulfamethoxazole in these strains. Here, we sequenced the conserved genes of the SXT element, including eex, setR, and int, from 59 V. cholerae O1 El Tor strains and extracted and assembled the intact SXT sequences from the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 18 publications
1
34
0
1
Order By: Relevance
“…To date, at least 89 SXT/R391-family ICEs have been identified (http://db-mml.sjtu.edu.cn/ICEberg/)26. Most ICEs have been investigated in V. cholerae 42728293031, which is the aetiological agent of the diarrhoeal disease cholera. The ICEs reported in Proteus strains including R997 (India)32, ICE Pmi USA1 (America)33, ICE Pmi Jpn1(Japan)16, ICE Pmi Spn1(Spain)24 and ICE Pmi Chn1(China)17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, at least 89 SXT/R391-family ICEs have been identified (http://db-mml.sjtu.edu.cn/ICEberg/)26. Most ICEs have been investigated in V. cholerae 42728293031, which is the aetiological agent of the diarrhoeal disease cholera. The ICEs reported in Proteus strains including R997 (India)32, ICE Pmi USA1 (America)33, ICE Pmi Jpn1(Japan)16, ICE Pmi Spn1(Spain)24 and ICE Pmi Chn1(China)17.…”
Section: Discussionmentioning
confidence: 99%
“…Three ICEs (cluster II in Fig. 1) with references including ICEs from V. cholerae strain ICDC-4210 (isolated from Jiangxi, China, in 1999)31 and P. mirabilis strain HI4320 (USA, 1986)33, indicated that the ICEs of this cluster may have appeared as early as 1986 and have been transmitted among different bacterial species and countries. Similarly, ICE Pvu CHN2213 in cluster III contained in a P. vulgaris strain isolated from food was closely related to the ICE MED6425 (from the Aegean Sea near Lebanon, 2000), which was between clusters I and II.…”
Section: Discussionmentioning
confidence: 99%
“…PCR was carried out in Thermal Cycler Eppendorf Mastercycler Nexus (Eppendorf, Hamburg, Germany) for detecting the presence of SXT element using primers specific for int, eex, att-prfC and setR genes. The primer and reaction conditions used were as described previously [13]. Primers specific for sul1, sul2 and sul3 genes for sulfamethoxazole resistance, dfrA1, dfr5 and dfr18 for trimethoprim resistance,…”
Section: Conventional Pcrmentioning
confidence: 99%
“…In fact, these SXT and closely-related elements are present in almost all V. cholerae clinical isolates and some environmental isolates from Asia and Africa [93] . A group of researcher has confirmed that the SXT elements were the vectors of genes conferring multidrug resistance in Chinese epidemic O1 V. cholerae to tetracycline and trimethoprimsulfamethoxazole [94] . Taken together, the resistance development limits the useful lifespan of antibiotic and Tan LTH et al results in the requirement for a constant introduction of new antibacterial compounds [95,96] .…”
Section: Emergence Of Antibiotic Resistant Vibrio Spmentioning
confidence: 99%